1998
DOI: 10.1063/1.366679
|View full text |Cite
|
Sign up to set email alerts
|

Growth of adhesive contacts for Maxwell viscoelastic spheres

Abstract: Coalescence of a Maxwell viscoelastic sphere to a frictionless and flat rigid plane is analyzed to study the transition from initial elastic adhesion to viscous sintering. Deformation is driven by surface tractions due to the surface energy. The formulation for surface forces consistently combines direct van der Waals attraction across the gap ahead of the contact edge with curvature-based tractions normal to the sphere surface. These two contributions to the surface traction result in two different modes of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 40 publications
2
67
0
Order By: Relevance
“…An interesting result of Jagota et al (20) is that, at short times when viscoelastic adhesive contact dominates, the contact growth behaves as a simple power law in time after the initial elastic JKR contact, i.e., a ∝ t 1/5 , remarkably different from the viscous flow model [1] that predicts a ∝ t 1/2 . Also, Jagota's numerical results showed that contact growth depends not only on R but also on another length scale, which has to do with the nature of intersurface attractions.…”
Section: Figmentioning
confidence: 96%
“…An interesting result of Jagota et al (20) is that, at short times when viscoelastic adhesive contact dominates, the contact growth behaves as a simple power law in time after the initial elastic JKR contact, i.e., a ∝ t 1/5 , remarkably different from the viscous flow model [1] that predicts a ∝ t 1/2 . Also, Jagota's numerical results showed that contact growth depends not only on R but also on another length scale, which has to do with the nature of intersurface attractions.…”
Section: Figmentioning
confidence: 96%
“…General purpose computational (e.g., finite element) methods [31,34,37,[116][117][118]. These methods typically represent the role of surface stress in a modular way, say as a surface finite element, which allows surface stress effects to be combined with nearly any form of bulk mechanical behavior.…”
Section: Analytical and Numerical Methodsmentioning
confidence: 99%
“…On the other hand, forces at a sintering neck, which is essentially an exterior crack, usually have been modeled based on surface tension and local curvature. 134 The difference between the two is illustrated in Fig. 17.…”
Section: (6) Adhesion and Sinteringmentioning
confidence: 99%
“…Moreover, there may be a regime of particle size in which sintering is controlled by direct attractive forces across the gap ahead of the neck, rather than by surface tension. 145 By combining both surface tension and direct attractive interactions, Jagota et al 134 have studied the problem of sintering of a Maxwell viscoelastic sphere to a rigid half space. Their analysis retrieves the known limits: initial elastic adhesion driven by direct attractive forces and final contact growth driven by surface tension.…”
Section: (6) Adhesion and Sinteringmentioning
confidence: 99%